2023
DOI: 10.3390/foods12050935
|View full text |Cite
|
Sign up to set email alerts
|

New Route to the Production of Almond Beverages Using Hydrodynamic Cavitation

Abstract: Perceived as a healthy food, almond beverages are gaining ever-increasing consumer preference across nonalcoholic vegetable beverages, ranking in first place among oilseed-based drinks. However, costly raw material; time and energy consuming pre- and posttreatments such as soaking, blanching and peeling; and thermal sterilization hinder their sustainability, affordability and spread. Hydrodynamic cavitation processes were applied, for the first time, as a single-unit operation with straightforward scalability,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…The measured velocities and the peak absorbance had standard deviations of ±1.5 and ±5%, respectively. Uncertainties in pressure and cavitation number were calculated using the manufacturer’s data sheets and uncertainty propagation method . Accordingly, the mean uncertainties in pressure, velocity, cavitation number, and peak absorbance are ±1.5, ±0.3, ±4, and ±5%, respectively.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The measured velocities and the peak absorbance had standard deviations of ±1.5 and ±5%, respectively. Uncertainties in pressure and cavitation number were calculated using the manufacturer’s data sheets and uncertainty propagation method . Accordingly, the mean uncertainties in pressure, velocity, cavitation number, and peak absorbance are ±1.5, ±0.3, ±4, and ±5%, respectively.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…There is an increasingly popular application of HC in particle dissolution and disintegration, ,, as well as physical and chemical processing. , For example, a study by Faraloni et al demonstrated the exceptional efficiency of hydrodynamic cavitation (HC) in food processing and material dissociation. The study showed that HC can produce high extraction yields and nutritional profiles comparable to those of a high-end commercial product.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters all need to be explored to determine if organic acid extraction during sample analysis is incomplete and needs improvement [49][50][51]. A more efficient treatment, feasible at large-scale such as hydrodynamic cavitation, may be necessary [52]. Finally, for organic acids, at the end of the simulated digestion, a significant difference was observed between the SMS and two samples: SMS-LS and SMS-MS (Dunnett's test, p = 0.04), suggesting a lower nutritional value when the residual sugar content is low in sugar sand.…”
Section: Evaluation Of the Digestibility Of Maple Syrup By-productsmentioning
confidence: 99%
“…The basic almond drink prepared in this study had a TPC of 121.27 mg/L, which is within the range of values reported in the literature. Manzoor et al (33) studied the effect of thermosonication of almond drinks and reported a TPC of 702.2 µg/g, while Faraloni et al (34) applied hydrodynamic cavitation and obtained up to 140 mg/kg of TPC depending on the applied processing conditions. Similarly, Ceylan (35) found TPC in almond drinks in the range of 102-553 mg/kg.…”
Section: Total Phenolic Contentmentioning
confidence: 99%